Combatting the Threat of Cybercrime in Nigeria: Examining Current Laws and Policies - Tsado, Lucy; Raufu, Abiodun; Ben-Edet, Emmanuel; Krakrafaa-Bestman, Doris (Journal of Applied And Theoretical Social Sciences, 2023)
Cybercrime has been a major global criminological challenge in recent years. Regarded as one of the epicenters of international Internet fraud, Nigeria is gaining notoriety as a cybercrime hotbed. With the continuing advancement in technological innovations and the growth of terrorism in Nigeria, cyberattacks are also a continuing threat. Efforts to tackle the threat of cybercrime have mainly been ineffective. Even though the Nigerian government has introduced measures to tackle the danger posed by cybercrime to economic and social growth, the piecemeal approach it has used in the past has yielded no tangible results. In this paper, we argue that cybercrime cannot be confronted by the Nigerian government alone without a comprehensive, holistic approach, including international cooperation. We examined the various strategies employed by the Nigerian government to curb cybercrime and why cyber criminality has been a malignant tumor that has refused to subside. We also outline some policy measures and recommendations